Educating Across Borders : The Case of a Dual Language Program on the U.S.-Mexico Border - De la Piedra, Maria Teresa Berta; Esquinca, Alberto; Araujo, Blanca E. (Book collections on Project MUSE., 2018)
Educating Across Borders is an ethnography of the learning experiences of transfronterizxs, border-crossing students who live on the U.S.-Mexico border, their lives spanning two countries and two languages. Authors María Teresa de la Piedra, Blanca Araujo, and Alberto Esquinca examine language practices and funds of knowledge these students use as learning resources to navigate through their binational, dual language school experiences. The authors, who themselves live and work on the border, question artificially created cultural and linguistic borders. To explore this issue, they employed participant-observation, focus groups, and individual interviews with teachers, administrators, and staff members to construct rich understandings of the experiences of transfronterizx students. These ethnographic accounts of their daily lives counter entrenched deficit perspectives about transnational learners. Drawing on border theory, immigration and border studies, funds of knowledge, and multimodal literacies, Educating Across Borders is a critical contribution toward the formation of a theory of physical and metaphorical border crossings that ethnic minoritized students in U.S. schools must make as they traverse the educational system.